The Badly Wounded Claws of the Gray Eagle: The BPS at the End of the Franco Regime - Alcántara Pérez, Pablo (Hispania Nova, 2024)
Abstract: The final years of the Franco dictator ship were moments of important anti-Franco mobilization, from different territories and social spectrums. On the other hand, repression also increased. In this state violence, the Social Political Brigade (BPS) played a relevant role, since it was the police in charge of political crimes and one of the pillars of the regime to confront “subversion.” The idea of this article is to analyze how the agents of this Corps acted against the different militancy against the dictatorship, its origins and its changes through out the dictatorship. Also see how the opposition faced this repression in the late Franco years, whether it faced it or not and with what intensity.